Harmony and Conflict in Jane Austen's Sense and Sensibility (1811): An Individual Psychological Approach - Praptomo, Dwi Indra, Drs. Abdillah Nugroho, M.Hum, Titis Setyabudi, S.S, M.Hum (2015)
DWI INDRA PRAPTOMO, A 320 090 109, HARMONY AND CONFLICT IN JANE AUSTEN'S NOVEL "SENSE AND SENSIBILITY" (1811) AN INDIVIDUAL PSYCHOLOGICAL APPROACH. RESEARCH PAPER. MUHAMMADIYAH UNIVERSITY OF SURAKARTA. 2014. The problem of this study is to reveal how major character reflects her harmony and conflict. The objective of this study is to analyze the novel based on the structural elements and to analyze the novel based on the individual psychological approach. The type of this research is qualitative research. Type of data of the study is novel taken from two data sources: primary and secondary. The primary data source is the Sense and Sensibility novel published in 1992 in London by Stephen Arkin itself. While the secondary data sources are other materials taken from books, author's biography, essay, comments, critics and internet related to the study. Both data are collected by conducting library research and analyzed by descriptive analysis. Based on the analysis, the researcher portrays some conclusions. First, based on the structural analysis of each elements, it shows that the character and characterization, setting, plot, point of view, style, and theme. Second, based on the individual psychology analysis, the study shows that the problem faced by the major character is his own psychology condition to decide the appropriate ways for his life.Jane Austen tells that the problem of the major character causes the conflict of her mental condition and then develop to become contradiction between inferiority feeling, striving to superiority, creative self style of life, social interest, functional finalism and it brings her into harmony and conflict because the influence of her personality. Keywords: Sense and Sensibility, harmony and conflict, and Individual Psychological Approach.